2008
DOI: 10.4103/0019-5359.40582
|View full text |Cite
|
Sign up to set email alerts
|

Current status of 5α-reductase inhibitors in the treatment of benign hyperplasia of prostate

Abstract: Benign prostatic hyperplasia (BPH) is a common problem in aging menof BPH include increased urinary frequency, urgency, intermittency; nocturia; decreased force of stream; hesitancy and straining that are usually associated with complications such as acute urinary retention, urinary incontinence, recurrent urinary tract infection, hematuria, renal failure, and bladder stone. [4][5][6][7][8][9] The primary goal for treating symptomatic BPH is to improve urine ß ow, for which both surgical and nonsurgical approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Dutasteride was found to improve urinary flow rate, decrease the risk of acute urinary retention and need for surgery by reducing the size of enlarged prostate. Improved efficacy of dutasteride (0.5 mg/day) over finasteride (5 mg/day) in terms of symptom score, maximal urinary flow rate and quality of life had also been published by Kumar, et al [32].…”
Section: Dutasteridementioning
confidence: 84%
See 1 more Smart Citation
“…Dutasteride was found to improve urinary flow rate, decrease the risk of acute urinary retention and need for surgery by reducing the size of enlarged prostate. Improved efficacy of dutasteride (0.5 mg/day) over finasteride (5 mg/day) in terms of symptom score, maximal urinary flow rate and quality of life had also been published by Kumar, et al [32].…”
Section: Dutasteridementioning
confidence: 84%
“…It is a competitive inhibitor of 5α-reductase type 2 with 10 fold high affinity than type 1 and forms a stable complex with enzyme ( Figure 4). It has been reported that at clinical doses of 5 mg/day in human, it decreases the prostate DHT level by 70-90%, thus resulting in decreased prostate volume or size and improved urinary flow rate in BPH patients [32]. It has neither androgenic, antiandrogenic, other hormone related properties, nor it interferes with the binding of T or DHT to the AR [33].…”
Section: α-Reductase Inhibitorsmentioning
confidence: 99%
“…It has been reported that at clinical doses of 5 mg/day in human beings, it decreases the prostate DHT level by 70 to 90%, thus resulting in decreased prostate volume or size and improved urinary flow rate. [2930] It has neither androgenic, antiandrogenic, other hormone related properties, nor it interferes with the binding of T or DHT to the androgen receptor. [31] The investigators found significant improvement in finasteride-treated groups in term of increased flow rates and decreased prostate-specific antigen level.…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%
“…[30] It was approved by US FDA in 2002 for the symptomatic treatment of BPH. Unlike finasteride, dutasteride has been reported to be a nonselective competitive inhibitor of both 5α-reductase type 1 and 5α-reductase type 2 isozymes.…”
Section: Androgen Deprivation Therapymentioning
confidence: 99%
“…[3] This fact was further confirm with the development of 5α reductase inhibitors, namely finasteride and dutasteride, which when given to BPH patients significantly reduced prostate size and DHT level in the prostate. [4][5][6] However, this conventional treatment for BPH is restricted because of associated side effects, such as erectile dysfunction, loss of libido, dizziness, gynaecomastia and upper respiratory tract infection. [7] Plants are important sources of therapeutic drugs and play a significant role of in the survival of the tribal and ethnic communities.…”
Section: Introductionmentioning
confidence: 99%